1966
DOI: 10.1007/bf02641187
|View full text |Cite
|
Sign up to set email alerts
|

Alternation of melting points in homologous series of long‐chain compounds

Abstract: The different possibilities of staeking of layers in long-chain compounds have been analyzed with reference to structural differences between even and odd members of homologous series. It has been possible to correlate packing differences with alternation of melting points and explain the alternation behavior completely on this basis. The theory can also be applied to surface films and mesomorphous phases. Alternation of enantiotropic transition temperatures and other physical properties are also discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
0
1

Year Published

1982
1982
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(38 citation statements)
references
References 20 publications
4
33
0
1
Order By: Relevance
“…Although these ideas now seem discordant with our views on covalent bonding (Burrows 1992), they perhaps relate to resonance within covalence bonding (Muller and Carl 2006). Larsson (1966) suggested that packing in the planes containing the end groups explained the effect. An increase in packing density will increases the intermolecular interactions, notably Van der Waals's forces.…”
Section: Odd-even Effectmentioning
confidence: 96%
See 1 more Smart Citation
“…Although these ideas now seem discordant with our views on covalent bonding (Burrows 1992), they perhaps relate to resonance within covalence bonding (Muller and Carl 2006). Larsson (1966) suggested that packing in the planes containing the end groups explained the effect. An increase in packing density will increases the intermolecular interactions, notably Van der Waals's forces.…”
Section: Odd-even Effectmentioning
confidence: 96%
“…Burrows 1992). Cappa et al (2007) and Larsson (1966) approached this from an atmospheric science perspective in relation the vapour pressure of (C 4 -C 10 ) dicarboxylic acids. The odd-even effect is often observed with longer chain compounds particularly in terms of the triple point of the mono-carboxylic acids and the Kraft temperature which relates to surfactant properties.…”
Section: Odd-even Effectmentioning
confidence: 98%
“…When the long alkyl/acyl chains are tilted with respect to methyl end group planes then the van der Waals interactions between methyl groups from opposite layers are usually different for the even-and odd chain length series. 24,25 Therefore, odd-even alternation is clearly observed when the alkyl chain packing is inclined with respect to the methyl end planes, but not when they are packed perpendicular to the methyl end planes. 14,25 The odd-even alternation in the calorimetric properties of dry and hydrated NAAEs as observed here suggests that the acyl and/or alkyl chains are tilted with respect to the respective methyl end planes in them.…”
Section: Chain Length Dependence Of Transition Enthalpy and Transitiomentioning
confidence: 92%
“…(3 Â 30 ml) and brine (total 90 ml); dried (Na 2 SO 4 ), and evaporated. FC (CH 2 Cl 2 / H 9.58,N 4.19;found: C 56.26,H 9.70,ethoxy]acetic Acid (Dithiodipropane-3,1-diyl) Ester (11). According to [25], a mixture of 7 (4.58 g, 25.7 mmol), CHCl 2 OMe (3.7 g, 32.1 mmol) and ZnCl 2 (0.18 g, 1.2 mmol) was stirred at r.t. for 1 h and refluxed 1 h under N 2 .…”
Section: Experimental Partmentioning
confidence: 99%
“…The (dithiodialkanediyl)bis[phthalimides] 4a ± f were obtained by treatment of (bromoalkyl)phthalimides 3a ± f with Na 2 S 2 O 3 and oxidation of the Bunte salts with I 2 in 70 ± 80% yield. The compounds 3b ± f show the well-known behavior of alternating melting points for homologuous series of substituted alkanes [10] [11]. The stable and easily isolated (dithiodialkanediyl)-bis[ammonium chlorides] 5a ± f were obtained in 60 ± 80% yield by treatment of the phthalimides 4a ± f with hydrazine followed by addition of hydrochloric acid.…”
mentioning
confidence: 99%